Peripheralization: the making of spatial dependencies and social injustice - Fischer-Tahir, Andrea; Naumann, Matthias (Springer VS, 2013)
With contributions by Andrea Fischer-Tahir, Matthias Naumann, Eren Düzgün, Benjamin Zachariah, Thilo Lang, Tim Leibert, Alexandru Banica, Marinela Istrate, Daniel Tudora, Anja Reichert-Schick, Sabine Beisswenger, Thomas Bürk, Dolarice Sátyro Maia, Arian Mahzouni, Antía Mato Bouzas.
Keywords: Aufsatzsammlung; Soziale Ungleichheit; Regionalpolitik; Regionalanalyse; Peripherer Raum